Completion of Ethical Dilemma and its Medicolegal Aspect in the Case of Pregnancy with History of Rheumatic Heart Disease: Penyelesaian Dilema Etika dan Aspek Medikolegalnya pada Kasus Kehamilan dengan Riwayat Penyakit Jantung Rheumatik - Taufik S. Ismail; Andy P. Meliala; Kulsum B. Syarifudin (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: To investigate more regarding the ethical dilemma resolution and medico-legal aspect of medical pregnancy termination due to preexisting Rheumatic Heart Disease (RHD).Methods: a Case report, presented a case of heart failure due to RHD in pregnancy, a 33-year-old patient in her third pregnancy with multiple valve disease including severe mitral stenosis, moderate mitral regurgitation, and mild tricuspid regurgitation. The patient came to the emergency ward due to shortness of breath worsening when she started becoming pregnant. The medical decision taken is very dilemma between continuing the pregnancy with the risk of endangering the mother's life or terminating the pregnancy with the risk of the mother losing her fetus. Results: After a joined conference that involved some medical, ethical, medicolegal and spiritual expertise discussing the best therapeutic options for patients, it was decided that the patient's condition was very high risk if the pregnancy was continued, using the minus malum principle, which is to take an actions with minimal risk, hence termination pregnancy is worse than the patient's death. Another ethical principle is beneficence which is for the good of the patient. The clinical ethics considered are medical indication and quality of life.Conclusion: The ethical concept should guide the obstetrician to reach ethically justified judgment regarding the balance between autonomy-based and beneficence-based obligation to the pregnant mother and the fetus. Women with RHD of reproductive age must receive early preconception evaluation and advice regarding the potential impact of pregnancy on their cardiovascular function.Keywords: ethical dilemma, medico-legal, pregnancy, rheumatic heart disease AbstrakTujuan: Menyelidiki lebih lanjut tentang penyelesaian dilemma etika dan tinjauana spekmedikolegal terhadap terminasi kehamilan medis karena Penyakit Jantung Rheumatik (PJR) yang sudah ada sebelumnya.Metode: Laporan kasus, disajikan sebuah kasus gagal jantung karena PJR pada kehamilan, seorang pasien berusia 33 tahun pada kehamilan ketiga dengan penyakit katup ganda termasuk stenosis mitral berat, regurgitasi mitral sedang, dan regurgitasi trikuspidringan. Pasien dating keruang gawat darurat karena napasnya yang pendek memburuk ketika mulai hamil. Keputusan medis yang diambil sangat dilematis antara meneruskan kehamilan dengan risiko membahayakan jiwa buat auterminasi kehamilan dengan risiko si ibu kehilangan janinnya.Hasil: Setelah dilakukan join conference yang melibatkan beberapa keahlian baik medik, etik, medikolegal maupun spiritual membicarakan pilihan terapi terbaik buat pasien maka diputuskan bahwa kondisi pasien sangat berisiko tinggi apabila kehamilan diteruskan, dengan menggunakan prinsip etika minus mallum yaitu mengambil tindakan yang lebih kecil keburukannya, maka terminasi kehamilan lebih kecil keburukannya dibandingkan kematian pasien. Prinsip etika yang lain adalah beneficence yaitu demi kebaikan pasien. Etika klinik yang dipertimbangkan adalah indikasi medis dan kualitas hidup.Kesimpulan: Konsepetis harus memandu ahli obstetrik untuk mencapai penilaian etis yang dibenarkan tentang keseimbangan antara kewajiban berbasis otonomi dan berbasis beneficence kepada ibu hamil dan janin. Perempuan dengan RHD usia reproduksi harus menerima evaluasi prakonsepsi dini dan saran mengenai dampak potensial kehamilan pada fungsi kardiovaskular mereka.Kata kunci: Dilemaetik, kehamilan, medikolegal, penyakit jantung rheumatik